PENGARUH MOTIVASI KERJA, SIKAP KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN LABUHANBATU SELATAN - Lia Ulfayani; Sumardi .; Yance Irawan Nasution; Yemki Satria; Herinov Helfi (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Problem of this study how influence of job motivation on performance. How influence of work attitude on performance. How influence of transformational leadership on performance. How influence job motivation, work attitude and transformational leadership on performance. The purpose of this study to determine and analyze the effect of job motivation on performance. Determine and analyze the effect of work attitude on performance. Determine and analyze the effect of transformational leadership on performance. Determine and analyze the effect of job motivation, work attitude and transformational leadership on performance. Sample in the study is 36 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job motivation variable has a positive and significant effect on performance. work attitude variable has a positive and significant effect on performance. transformational leadership variable has a positive and significant effect on performance. Job motivation, work attitude and transformational leadership variable has a positive and significant effect on performance.